2018
DOI: 10.3847/1538-4357/aada06
|View full text |Cite
|
Sign up to set email alerts
|

A Faraday Rotation Study of the Stellar Bubble and H ii Region Associated with the W4 Complex

Abstract: We utilized the Very Large Array to make multifrequency polarization measurements of 20 radio sources viewed through the IC 1805 HII region and "Superbubble". The measurements at frequencies between 4.33 and 7.76 GHz yield Faraday rotation measures (RMs) along 27 lines of sight to these sources. The RMs are used to probe the plasma structure of the IC 1805 HII region and to test the degree to which the Galactic magnetic field is heavily modified (amplified) by the dynamics of the HII region. We find that IC 18… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 105 publications
1
22
0
Order By: Relevance
“…• 5 with a contrast ∼ 1 K in the THOR continuum image, but no excess that traces the higher RM s. On the other hand, free-free emission from super bubble walls is clearly detected around W4 (Costa & Spangler 2018) and W47 . The high RM sources of Costa & Spangler (2018), including O10, are enclosed by the contour T B = 5.7 K, while the Galactic background is in the range 4.9 K to 5.1 K. Also, Gray et al (1999) found that depolarization of diffuse emission is closely correlated with total intensity. A stronger mean magnetic field B 15 µG (B 45 µG for RM ≈ 3 × 10 3 rad m −2 ) would reduce the implied emission measure beyond detection in the radio continuum image.…”
Section: Discussionmentioning
confidence: 95%
“…• 5 with a contrast ∼ 1 K in the THOR continuum image, but no excess that traces the higher RM s. On the other hand, free-free emission from super bubble walls is clearly detected around W4 (Costa & Spangler 2018) and W47 . The high RM sources of Costa & Spangler (2018), including O10, are enclosed by the contour T B = 5.7 K, while the Galactic background is in the range 4.9 K to 5.1 K. Also, Gray et al (1999) found that depolarization of diffuse emission is closely correlated with total intensity. A stronger mean magnetic field B 15 µG (B 45 µG for RM ≈ 3 × 10 3 rad m −2 ) would reduce the implied emission measure beyond detection in the radio continuum image.…”
Section: Discussionmentioning
confidence: 95%
“…A few sources show conspicuously large deviations between new and old RM measurements. Both of the sources that were also present in the Tabara & Inoue (1980) catalog have very different RMs (>100 rad m −2 difference), as do two of the sources from Costa & Spangler (2018). However, all 4 of these sources show signs of Faraday complexity in the older measurements: significant changes in polarized fraction at different frequencies for the Tabara & Inoue (1980) RMs, and large linear fit residuals for the Costa & Spangler (2018) RMs.…”
Section: Comparison With Previous Catalogsmentioning
confidence: 90%
“…Interstellar objects such as supernova remnants, planetary nebulae, H IIregions, globular clusters, and gigantic radio loops are all shaped by the influence of the Galactic magnetic field (e.g., [127][128][129][130]); see also Section 2.3.2. The magnetic content of high velocity clouds (HVCs) such as the Smith Cloud [131] is important for their longevity.…”
Section: The Milky Waymentioning
confidence: 99%
“…The SKA will test this through sensitivity to polarized emission from large grains aligned with the magnetic field, which will also probe grain growth in these disks [168,169]. Magnetic fields in the ISM surrounding star-forming regions both influence the evolution of and may also be impacted by H II regions [129,170]. The SKA will be able to probe the detailed physical conditions in and around H II regions [171,172].…”
Section: The Interstellar Medium and Star Formationmentioning
confidence: 99%